Volume 7: Turbomachinery, Parts A, B, and C 2011
DOI: 10.1115/gt2011-46829
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Various Turbulence Models in a High Pressure Ratio Centrifugal Compressor With an Object Oriented CFD Code

Abstract: The flow field in a high pressure ratio centrifugal compressor with vaneless diffuser has been investigated numerically. Main goal is to assess the influence of various turbulence models suitable for internal flows with adverse pressure gradient. The numerical analysis is performed with a 3D RANS in-house modified solver based on an object-oriented open-source library. According to previous studies from varying authors, the turbulence model is believed to be the key parameter for the discrepancy between experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The inconsistency not only occurs in the current research, but was also reported by former researchers. 25,26 It is also noticed in Figure 6 that inconsistency also exists for the surge point prediction. In this steady case, the surge point is defined as the converged point with the highest backpressure.…”
Section: Optimization Methodsmentioning
confidence: 81%
“…The inconsistency not only occurs in the current research, but was also reported by former researchers. 25,26 It is also noticed in Figure 6 that inconsistency also exists for the surge point prediction. In this steady case, the surge point is defined as the converged point with the highest backpressure.…”
Section: Optimization Methodsmentioning
confidence: 81%
“…Furthermore left operating range is correctly computed if the unsteadiness are resolved. Finally the possibility to model hub cavity in open centrifugal compressor impellers and the possibility of using non-matching blocks for tip domain should increase the accuracy of CFD computations on predicting operating range and quantitative level of efficiency that has been historically a weak point for open impellers like shown in [21] …”
Section: Discussionmentioning
confidence: 99%
“…Numerical approximations and turbulence modeling increase also the source of errors. According to the study of Mangani [21], more advanced turbulence models are not sufficient to capture the discrepancy between experimental and numerical results, especially at high pressure ratios and high mass-flow on open centrifugal compressor impellers. In the present study full cavity meshing has been included and accurate reproduction of the stage geometry including fillets and upstream stage has been used.…”
Section: Overall Performancementioning
confidence: 99%
“…The stage averaging at the interface incurs a one-time mixing loss which accounts for timeaveraged interaction effects. The Shear Stress Transport (SST) turbulence model of Menter (1994) was employed because of its success in modeling flows in an adverse pressure gradient, and Mangani, Casartelli, and Mauri (2012) have proved that this turbulence model is suitable for centrifugal compressor calculations. A 'high resolution' advection scheme (ANSYS, 2011a) was employed for all equations except for the turbulence equation, which uses a first-order upwind scheme.…”
Section: Numerical Schemementioning
confidence: 99%